Spatio-temporal dynamics of fish assemblages at an offshore wind farm and a comparison with mature artificial reefs - Kwang Tsao Shao; Ching Han Chang; Ching Yi Chen; Lin Tai Ho; Yi Ta Shao; Hsin-Chieh Chiang; Wei-Ning Lee; Hsien Ju Tsai; Tien-Yu Huang; Chun-Yu Chang (Frontiers in Marine Science, 2026)
Introduction Offshore wind farms (OWFs) are vital for sustainable energy. The underwater foundations of those wind turbines provide a complex structure that creates new habitats and attracts fishes. However, whether OWFs had the same ecological function as purpose-built artificial reef (AR) and how they alter the original fish community remain unclear. Methods To evaluate the spatial and temporal variations in fish assemblages, we conducted a multi-part investigation at the Formosa Wind Farm, located off the coast of Miaoli County, Taiwan. Temporal changes were assessed through SCUBA surveys at turbine foundations in 2017, 2018, and 2025, with the 2025 data allowing for a direct comparison with the nearby existing artificial reefs. To assess spatial effects, pole-and-line surveys were conducted from Apr to Oct in 2024 and 2025 at varying distances from the turbines. Results Our investigation documented 86 species of reef-associated fishes exclusively within 50 m of turbine foundations; none were caught in the surrounding sandy areas or documented in pervious fishery records. The results demonstrated that fish assemblages around the turbine piles changed successively over the years. Although the species composition in 2025 differed between the OWF and the established AR sites, key ecological metrics such as species richness, diversity, and trophic structures showed no significant differences. Discussion These findings demonstrated that the underwater structure of offshore wind turbines can function as AR, creating novel reef habitats and supporting reef-associated fish community within a finite spatial extent. Overall, OWFs may provide ecological benefits in addition to renewable energy, highlighting their potential role in balancing energy development with marine conservation.